2017
DOI: 10.1161/hypertensionaha.116.08459
|View full text |Cite
|
Sign up to set email alerts
|

Increased Aortic Calcification Is Associated With Arterial Stiffness Progression in Multiethnic Middle-Aged Men

Abstract: Arterial stiffness is established as an independent predictor of cardiovascular morbidity and mortality. The objective was to prospectively evaluate association of aortic calcification burden with progression of arterial stiffness in population-based samples of healthy middle-aged men from ERA JUMP cohort. Men (n=635) aged 40–49 (207 White American, 45 African American, 142 Japanese American and 241 Japanese in Japan) were examined at baseline and 4–7 years later. Aortic calcification was evaluated from level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 53 publications
(59 reference statements)
4
46
0
2
Order By: Relevance
“…One possible explanation for this finding may be that calcium deposits in vascular structures cause vascular calcification, which was reported to share a significantly positive association with arterial stiffness in both a healthy population [29] and ESRD patients [30]. This finding deserves special consideration given the high incidence of chronic kidney disease-mineral and bone disorder (CKD-MBD) and the widespread use of calcium-based binders in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 98%
“…One possible explanation for this finding may be that calcium deposits in vascular structures cause vascular calcification, which was reported to share a significantly positive association with arterial stiffness in both a healthy population [29] and ESRD patients [30]. This finding deserves special consideration given the high incidence of chronic kidney disease-mineral and bone disorder (CKD-MBD) and the widespread use of calcium-based binders in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 98%
“…Of note, several studies have recently reported that calcification of the aorta is associated positively with arterial stiffening both in hemodialysis patients [37,38] and in other cohorts [39][40][41][42][43] .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, some reports have indicated that increased iron in vitro enhances calcification of both endothelial (Nanami et al, ) and smooth muscle cells (Kawada et al, ) through inflammation and oxidative stress. In addition, it has been proposed that aortic calcification may be causally linked to arterial stiffness and increased PWV in humans (Guo et al, ; Sekikawa et al, ; Tsao et al, ) and a rat model of vascular disease (Ng et al, ). However, our data indicate that this short‐term protocol of iron‐overload was unable to induce significant calcification of the rat aorta, and treatment with losartan did not modify this parameter.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, some reports have indicated that increased iron in vitro enhances calcification of both endothelial (Nanami et al, 2005) and smooth muscle cells (Kawada et al, 2018) through inflammation and oxidative stress. In addition, it has been proposed that aortic calcification may be causally linked to arterial stiffness and increased PWV in humans (Guo et al, 2017;Sekikawa et al, 2012;Tsao et al, 2014) and a rat model of vascular disease (Ng et al, 2011).…”
Section: Discussionmentioning
confidence: 99%